Nasopharyngeal cancers in University of Port Harcourt teaching hospital: a five year review - Uju, Ibekwe Matilda (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Nasopharyngeal cancer though an uncommon head and neck cancer, has high morbidity and mortality. It is a cancer that has peculiar geographic variations and hence has been studied by a lot of researchers globally. It however has not been studied as an entity in the South region. This study was to determine the clinical and histologic presentations as well as the prevalence of this disease in Port Harcourt. Methods: Hospital based retrospective review of all patients with confirmed diagnosis of nasopharyngeal cancer seen within the period of January 2014 to December 2018 at ENT Department University of Port Harcourt teaching hospital. The hospital records were the source of data. The demographics, clinical presentations, histology, investigations and outcome were all collated from the records and were analyzed with IBM SPSS version 25. Results: Forty-one patients were studied with age range of 12-85 years. The mean age was 43±15.1 years. Male to female ratio was 1.2:1. Age 40 to 49 years was the most affected. Nasopharyngeal carcinoma was the commonest cancer recorded 68.29% followed by non-Hodgkin’s lymphoma 19.5%. Keratinizing squamous cell carcinoma was the commonest histologic type 43.9%. Commonest symptoms were neck swelling and nasal congestion 24.55%. Age distribution showed a statistical difference with histology of cancer. Mortality of 4.87 was recorded; the rest was lost to follow up. Conclusions: Nasopharyngeal carcinoma is the commonest cancer in the nasopharynx. It is significantly related with age. Patients often present late and it has very high morbidity and mortality rate. Attention to early vague symptoms will enhance early diagnosis, treatment therefore prognosis.